2012
DOI: 10.5543/tkda.2012.43078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endothelial Functions in Patients With Behcet's Disease Without Overt Vascular Involvement

Abstract: Vascular endothelial function is impaired in BD. Brachial artery Doppler USG is a reliable and reproducible method to establish changes in vascular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…A previous study showed increased cIMT values in BD patients with vascular involvement compared to those without vascular involvement (27). In another study, the cIMT values of BD patients with vascular involvement were found to be similar to the control group (33). Our study also showed no significant difference between cIMT values in cases with and without vascular involvement.…”
Section: Discussionsupporting
confidence: 58%
“…A previous study showed increased cIMT values in BD patients with vascular involvement compared to those without vascular involvement (27). In another study, the cIMT values of BD patients with vascular involvement were found to be similar to the control group (33). Our study also showed no significant difference between cIMT values in cases with and without vascular involvement.…”
Section: Discussionsupporting
confidence: 58%
“…1), 24 studies met the criteria for inclusion in the analysis: 9 investigated FMD and/or EMD [18][19][20][21][22][23][24][25][26], 11 IMT [8,[27][28][29][30][31][32][33][34][35][36] and 4 investigated both [37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…Ancak Behçet Hastalığının yaygın olarak görüldüğü bölgelerde ailesel geçiş de görülebilmektedir (9). Hastalığın önemli komplikasyonları ve hastalığa bağ-lı ölümler, vasküler tutuluma bağlı ortaya çıkan, vaskülit, tromboemboli ve anevrizma nedeniyle oluşmaktadır (10).…”
Section: Discussionunclassified